2014
DOI: 10.1111/1469-0691.12222
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of Ganciclovir-related neutropenia after allogeneic stem cell transplantation: a retrospective monocentre study on 547 patients

Abstract: Cytomegalovirus (CMV) infection is a serious complication that may occur in the weeks or months following bone marrow transplantation. However, both Ganciclovir and the CMV infection itself can cause marrow toxicity, notably neutropenia, that may consequently expose these immunosuppressed patients to life-threatening bacterial and/or fungal infections. The aim of this retrospective study was to identify factors associated with the occurrence of grade III-IV neutropenia among patients receiving pre-emptive Ganc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…CMV-associated neutropenia (absolute neutrophil count , 500 per mm 3 within 60 days after CMV reactivation) was also evaluated as a timedependent risk factor compared with patients who had CMV reactivation without subsequent neutropenia. 15 Peak acute GVHD (grades 0-1, 2, or 3-4) was graded according to standard definitions and analyzed in a timedependent manner. 16 Multivariable regression models were constructed in a stepwise manner.…”
Section: Discussionmentioning
confidence: 99%
“…CMV-associated neutropenia (absolute neutrophil count , 500 per mm 3 within 60 days after CMV reactivation) was also evaluated as a timedependent risk factor compared with patients who had CMV reactivation without subsequent neutropenia. 15 Peak acute GVHD (grades 0-1, 2, or 3-4) was graded according to standard definitions and analyzed in a timedependent manner. 16 Multivariable regression models were constructed in a stepwise manner.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Ganciclovir is principally excreted via the kidneys. Reduced renal function has been shown to prolong the halflife of ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
“…Our results regarding a low WBC count as a risk factor for ganciclovirinduced leukopenia are consistent with the findings of previous studies. [8][9][10] Therefore, special attention should be paid to patients with low WBC counts (<6000 cells/mm 3 ) receiving a high ganciclovir dose (≥12 mg/kg/d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these drugs are considered effective strategies for preventing CMV disease early after transplantation, they are associated with drug-related toxicities (myelosuppressive and immunosuppressive effects) [78] and they have been found to impair and delay the development of CMV-specific CTLs [50, 79]. Lilleri et al have shown that patients treated pre-emptively developed protection against CMV at a median time of 139 days compared to those that resolved CMV infection or did not have infection (median time 70 days) [52,80].…”
Section: Conditioning Regimensmentioning
confidence: 99%